Towards INDUSTRY 4.0: a case STUDY in ornamental stone sector - Silva, Agostinho da (2021)
A movement to mobilize the Portuguese Ornamental (OS) sector to reduce waste and improve flexibility began in 2004. Boosted by R&D Mobilizing Projects in consortium and fostered by two of the Sustainable Development Goals (SDG9 and SDG12), this mobilization resulted in a new generation of technologies, concepts and innovative practices, matching the needs of Portuguese OS companies, stressing an integrated approach to European Competitiveness that should be fostered by a sustainable industrial policy, combined with innovation and skills. Bearing in mind that the Sustainable Development Goals (SDG) are the blueprint to achieve a better and more sustainable future for all, and considering the importance of following the goals and guidelines of SDGs 9 and 12 in the industrial processes optimization achievement in the Portuguese OS sector, the following research question arises: What is the impact of the R&D Mobilizing Projects on the efficiency and image of Portuguese OS companies?